2012
DOI: 10.1039/c1nr11401h
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor core/shell silicananoparticles for in vivo and ex vivo imaging

Abstract: Biocompatible highly bright silica nanoparticles were designed, prepared and tested in small living organisms for both in vivo and ex vivo imaging. The results that we report here demonstrate that they are suitable for optical imaging applications as a possible alternative to commercially available fluorescent materials including quantum dots. Moreover, the tunability of their photophysical properties, which was enhanced by the use of different dyes as doping agents, constitutes a very important added value in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…For this purpose, NOD/SCID mice were injected intrasplenically with the highly metastatic CRC cell line HCT-116 m. In this well-established model, 21-28 days after cell injection animals develop a pseudo-orthotopic primary tumor in the spleen and several secondary tumors into the liver 14 Within this time frame, we injected either control or CGIYRLRStargeted single-or dual-color SPNs into the caudal vein and let them circulate for increasing periods of time starting from 1 h. This choice was based on our recently published data, showing a peak in the fluorescence emission in different organs, including the liver, during the first hour after untargeted SPN injection and a subsequent decrease with time. 5 Consistently, we observed a good reduction of nonspecific fluorescence (ie, the signals of untargeted SPNs in target tissues, and/or of targeted SPNs in nontarget tissues) after 6 h, maintaining this optimal signal-to-background ratio even after 16-24 h. A very similar outcome was obtained with CGVYSLRS-SPNs (data not shown). Nontargeted contrast agents have the disadvantage of being quickly removed from the bloodstream, thus requiring analysis to be performed shortly after injection (usually in the period of just minutes).…”
Section: Set-up Of Animal Models Of Human Metastatic Crc For Targetedsupporting
confidence: 82%
See 2 more Smart Citations
“…For this purpose, NOD/SCID mice were injected intrasplenically with the highly metastatic CRC cell line HCT-116 m. In this well-established model, 21-28 days after cell injection animals develop a pseudo-orthotopic primary tumor in the spleen and several secondary tumors into the liver 14 Within this time frame, we injected either control or CGIYRLRStargeted single-or dual-color SPNs into the caudal vein and let them circulate for increasing periods of time starting from 1 h. This choice was based on our recently published data, showing a peak in the fluorescence emission in different organs, including the liver, during the first hour after untargeted SPN injection and a subsequent decrease with time. 5 Consistently, we observed a good reduction of nonspecific fluorescence (ie, the signals of untargeted SPNs in target tissues, and/or of targeted SPNs in nontarget tissues) after 6 h, maintaining this optimal signal-to-background ratio even after 16-24 h. A very similar outcome was obtained with CGVYSLRS-SPNs (data not shown). Nontargeted contrast agents have the disadvantage of being quickly removed from the bloodstream, thus requiring analysis to be performed shortly after injection (usually in the period of just minutes).…”
Section: Set-up Of Animal Models Of Human Metastatic Crc For Targetedsupporting
confidence: 82%
“…Often, this does not enable precise quantifications or allow for repeated analyses. Conversely, we recently demonstrated that SPNs (including untargeted) persist in the bloodstream for up to 3 h. 5 The results of the experimental set-up described above suggest that clearance of untargeted nanoparticles is paralleled by specific accumulation of targeted SPNs that remains constant for longer periods (up to 24 h). The possibility of exploiting such a wide time frame for diagnostic imaging of hepatic micrometastases further supports translation into clinical applications.…”
Section: Set-up Of Animal Models Of Human Metastatic Crc For Targetedmentioning
confidence: 91%
See 1 more Smart Citation
“…9,25 Covalent doping of the silica core with alkoxysilane derivatized dyes produces PluS NPs that are very bright, with luminescent properties that were exploited in several fields, 26 such as the development of chemosensors, 27,28 fluorescent photoswitchable NPs, 29 NPs for electrochemiluminescence applications, 30,31 in vivo FOI, 5,9 and targeted fluorescence imaging. 9,32 Our previous findings have documented efficient cell internalization and lack of cytotoxicity of PluS NPs in some in vitro and in vivo assays.…”
mentioning
confidence: 99%
“…In reality, this apparently simple looking reaction system has to face several difficulties before an appreciable signal is received by the photo-detector to give an analysable dataset. With the rapid emergence of nanotechnology during last few decades, some of the critical problems have been solved [1][2][3][4][5]. However, a large number of unresolved issues still remain there.…”
mentioning
confidence: 99%